Lutas, repressão e conquistas: as experiências dos trabalhadores rurais na junta de conciliação e julgamento de Nazaré da Mata no contexto do golpe civil-militar (1963-1966) - Melo Junior, Ademir Bezerra de (2019)
This dissertation seeks to analyze the experiences of rural workers in the Council of Conciliation and Judgment of Nazaré da Mata between 1963 and 1966. To this end, it seeks to reflect on the most striking characteristics of the labor relations in force in the sugarcane zone of Pernambuco, in order to broaden the possibilities of questioning the data observed from the research carried out in the final records of the Labor Court. In those years workers gained the right to their labor rights, with the promulgation of the Rural Worker Statute (Estatuto do Trabalhador Rural - ETR) in 1963, and in the case of Pernambuco, after a series of parallel works in the sugar and alcohol sector, imposed the Field Agreement on Miguel Arraes's new rulers, a period in which, for the first time, they were supported by a framework of democratic guarantees in the countryside. This brief period of conquest was abruptly hit by the coup of 1964, where the workers 'demand movements were brutally persecuted and the police again became the owners' henchman. Thus was inaugurated a new moment, when the demand existed before the labor, a subversive element contrary to the notion of National security and a social order. In this sense, people sought the possibilities and limits of the experiences of rural workers in the court, and as they were marked by the history of labor relations, as the new plan was not started with the beginning of the exception regime.